Multiple Realizability in the Nature of the Mind and Its Implications for SETI - Oyelakin, Richard Taye (Conatus - Journal of Philosophy, 2025)
Responding to Putnam’s computational hypothesis of the mind and the adoption of the Turing machine, it is argued by Churchland and Searle (biological naturalists) that the implementing organic structure is necessary in understanding the nature of mental states. This paper notes that if the term “necessity” is understood in terms of “withoutness,” then it is argued, from the idea of multiple realizability, that no particular implementing structure is necessary to the nature of the abstract mental state. Furthermore, drawing implications from the analysis, the paper shows how limited and unjustified human understanding and generalizations about the issue of mental states can be when viewed only from an anthropocentric perspective, and the dire implications this brings on the search for extraterrestrial intelligence (SETI). The paper concludes that there is a need to review our methodology and reorient our technology to make a more promising search. The paper employs philosophical argumentation and analysis as tools of assessment of the metaphysical hypothesis.